Kesiapan Mahasiswa Pendidikan Guru untuk Menyelenggarakan Proses Pembelajaran Online - Muhd Odha Meditamar; Eko Sujadi; Eka Putra; Wisnarni Wisnarni (SAP (Susunan Artikel Pendidikan), 2022)
COVID-19 has a significant impact on various aspects, one of which is the learning process. This study aims to describe the readiness of teacher education students to organize online learning. The method used in this research was mixed methods. Ninety-seven students of the Islamic Religious Education Study Program IAIN Kerinci filled in a survey from November to December 2021. For the purposes of qualitative data, 3 people participated, including the Head of the Department, the Dean and the Vice Rector for Academic. The researcher adapted the research scale developed by Hung regarding the readiness of teachers to carry out online learning. Qualitative data collection was carried out using the interview method. All data was analyzed by descriptive statistics, Man-Whitnney Test and Kruskal-Wallis. Qualitative research data were analyzed using an interactive analysis model. The results showed that the readiness of teacher education students to conduct online learning was categorized as high. Based on the univariate analysis test, there was no difference in the readiness of teacher education students to conduct online learning based on the variables of gender, length of time accessing the internet in a day and the experience of participating in online learning. Universities have made several efforts to equip students with the skills to organize online learning. It is suggested to university to design a curriculum that is in accordance with the current and future learning needs.